Modified Presplit Blast Design and its Implementation to Control Near Field Blast Vibrations - Rasagna, D.L.S.; Reddy, K.S.N.; Singh, Sanjay; Das, Sudip (Global Journal of Earth Science and Engineering, 2021)
The development of urban infrastructure projects like metro rail projects in the major cities in India is one of the challenging tasks due to several site construction and operating constraints. These rapid transit systems (RTS) are conceived to minimise traffic congestion by providing commuters with fast and efficient transportation alternatives. One such project is the Phase-II of the ongoing Bangalore Underground Metrorail Project. The design and construction of the metro rail project require sound engineering judgment and field experience on envisaged strata conditions along the proposed route alignment. The important factors that govern the excavation cycle depend on Rock mass material properties, efficient blast design and construction performance. All these considerations needs to be evaluated for achieving safe, cost-effective excavation design layouts. Proper blast design and safe blasting operations play a key role in achieving good fragmentation, minimising over break and equipment downtime. Site-specific innovative methods on controlled blasting techniques are being experimented with and demonstrated to minimise the ground vibrations. The major challenge lies with the design of efficient and smooth wall blasting techniques to safeguard the old heritage buildings and other subsurface structures and utilities.